From motivation to practice: A qualitative study of university students’ strategies and expectations in Indonesia’s teaching campus program for elementary schools - Apoko, Tri Wintolo; Yusnawati, Yusnawati (Asatiza: Jurnal Pendidikan, 2025)
The Teaching Campus Program (TCP), a strategic initiative under Indonesia’s Merdeka Belajar (Emancipated Learning) policy, aims to enhance students’ pedagogical skills while supporting educational equity by placing university students in under-resourced schools. This study explores TCP students’  motivations, implementation plans, and expectations. The method employed in this study was a qualitative design. Using qualitative data gathered from semi-structured interviews with six students drawing on purposive sampling, the study applied three-step analysis model: data condensation, data display, and conclusion drawing. The findings revealed strong motivations in enhancing educational quality in Indonesia through their planning on some innovative methods such as gamification for promoting literacy and numeracy activities. In addition, they expected to enhance student engagement and school performance. To ensure the sustainability of the program, it is recommended that TCP initiatives be institutionalized through strategic partnerships between universities and schools, and supported by national education policies that integrate TCP into teacher training frameworks and school improvement agendas.